The Effect of Padded Adhesive Dressing and Static Body Position on Sacral Interface Pressure. Issue 8 (22nd December 2021) - Seu, Michelle; Bhat, Deepa; Wong, Alison; Wong, Michael; Nojoomi, Matthew; Padula, William; Sacks, Justin M.
Abstract : Objectives: Padded adhesive bandages are frequently used in the inpatient setting for sacral pressure injury prevention, but it is unclear whether they truly decrease interface pressure. We hypothesized such devices reduce sacral peak interface pressure in the supine position, which would be further reduced in 30-degree reclined and upright seated positions. Methods: Study participants rested with their sacrum on a pressure-sensing mat, in 3 positions, for 30 seconds each: (1) sitting upright; (2) supine; and (3) supine against 30-degree wedge. Measurements were made with and without a padded adhesive bandage overlying the sacrum. Age, sex, and body mass index (BMI) were collected. These variables were entered sequentially, in an a priori order to construct a linear mixed-effects model. Results: Forty healthy adults participated. After controlling for by-subject variation, age, and sex, BMI did not influence peak sacral pressure ( P = 0.22), although the effect of body position was significant ( P < 0.01). Subsequent addition of padded adhesive dressing was nonsignificant ( P = 0.17); sacral peak pressure was similar with a padded adhesive dressing (247.8 ± 147.3 mm Hg) or without (mean ± standard deviation = 229.8 ± 127.7 mm Hg). Lastly, there was no significant interaction between BMI and body position ( P = 0.11). Conclusions: Padded adhesive bandages did not reduce interface pressure in any position. Sacral pressure was highest in the supine position and was not specifically affected by BMI. If padded bandages provide clinically significant reduction in pressure injury incidence, it is not simply through the reduction of interface pressure.